2000
DOI: 10.1046/j.1365-2575.2000.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Whose job is it anyway?: organizational information competencies for value creation

Abstract: Abstract. Research highlights that most business managers continue to be dissatisfied with the value they perceive they are deriving from their organization's information systems investments. On examining the literature, the dominant perspective is that creating value through information systems is primarily the responsibility of the IS function. Accordingly, to address this chronic malaise, attention generally focuses on the IS function with proposed prescriptions ranging from re‐skilling the IS professional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 95 publications
1
55
0
Order By: Relevance
“…Although the literature is rather limited, with respect to benefits realization competences, two pieces of work were particularly influential in shaping our model: the 'information competences' framework (Peppard et al, 2000;Peppard & Ward, 2004) helped in structuring our framework, whilst the process model for benefits management (Peppard et al, 2007;Ward et al, 1996;Ward & Daniel, 2006;Ward et al, 2007) influenced its content. Based upon the literature review, four distinct competences were ultimately identified which should enhance an organization's ability to realize value from their IT investments, on a more consistent basis:…”
Section: The Benefits Realization Competences Frameworkmentioning
confidence: 99%
“…Although the literature is rather limited, with respect to benefits realization competences, two pieces of work were particularly influential in shaping our model: the 'information competences' framework (Peppard et al, 2000;Peppard & Ward, 2004) helped in structuring our framework, whilst the process model for benefits management (Peppard et al, 2007;Ward et al, 1996;Ward & Daniel, 2006;Ward et al, 2007) influenced its content. Based upon the literature review, four distinct competences were ultimately identified which should enhance an organization's ability to realize value from their IT investments, on a more consistent basis:…”
Section: The Benefits Realization Competences Frameworkmentioning
confidence: 99%
“…3 RBV has also aroused interest in the IS community [72][73][74][75][76]. These studies focused on large organizations, whereas our study concerns small companies.…”
Section: Discussionmentioning
confidence: 99%
“…A large volume of research has been done on IT governance and benefits realisation framework [1-8, 10, 11], [10,11], [15][16][17], [18], [19][20][21][22], [23], [24,25]. Whilst some of this research is focused on the benefit definition from procurement contracting perspective, others are focused on driving knowledge, on continuous benefit realisation review process, the benefit management of information systems, the benefit-strategy-solution mapping, the benefit of IT and R&D, the benefit of IT and Business alignment, etc.…”
Section: Defuzzification For Benefit Realizationmentioning
confidence: 99%